The Limitations of Science and Its Implications in Human Life - Putri, Davina Dwi Yulia; Putra, Dwi Rizqi Syah; Susanti, Eva; Mahardika, I Ketut; Mahmudi, Kendid; Zaki, Salman Faris Az (International Journal of Education, Information Technology, and Others, 2024)
Science has made a major contribution in advancing human civilization. However, it is important to recognize that science has inherent limitations. This limitation arises from the scientific method which relies on empirical observation and experimentation, making it difficult to study phenomena that are subjective or spiritual in nature. In addition, science is also limited in predicting random or complex events. The implications of these limitations of science are far-reaching, ranging from science's inability to answer questions about the meaning of life to difficulties in making ethical decisions involving technology. A deep understanding of the limitations of science can help society to appreciate the role of science in life while remaining aware of the importance of other values ​​such as religion, arts and humanities. In this way, humans can build a more holistic and balanced world view